2005
DOI: 10.1038/sj.emboj.7600820
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Epstein–Barr virus EBNA-LP transcriptional coactivation by Sp100

Abstract: The Epstein-Barr virus (EBV) EBNA-LP protein is important for EBV-mediated B-cell immortalization and is a potent gene-specific coactivator of the viral transcriptional activator, EBNA2. The mechanism(s) by which EBNA-LP functions as a coactivator remains an important question in the biology of EBV-induced B-cell immortalization. In this study, we found that EBNA-LP interacts with the promyelocytic leukemia nuclear body (PML NB)-associated protein Sp100 and displaces Sp100 and heterochromatin protein 1a (HP1a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 65 publications
(102 reference statements)
3
84
1
Order By: Relevance
“…Sp100, yet another major PML NBs component, has been implicated in repression of HSV-1 gene expression (Negorev et al, 2006) and in the regulation of Epstein-Barr virus transcription (Ling et al, 2005). It is confirmed that Sp100 is also involved in HSV-1 genome repression in the absence of ICP0 in human fibroblasts by the observation that depletion of Sp100 results in a similar increase in ICP0-null mutant gene expression (Everett et al, 2008a).…”
Section: Pml/sp100-related Repression Mechanism In the Absence Of Icp0supporting
confidence: 66%
“…Sp100, yet another major PML NBs component, has been implicated in repression of HSV-1 gene expression (Negorev et al, 2006) and in the regulation of Epstein-Barr virus transcription (Ling et al, 2005). It is confirmed that Sp100 is also involved in HSV-1 genome repression in the absence of ICP0 in human fibroblasts by the observation that depletion of Sp100 results in a similar increase in ICP0-null mutant gene expression (Everett et al, 2008a).…”
Section: Pml/sp100-related Repression Mechanism In the Absence Of Icp0supporting
confidence: 66%
“…Genetic variation in SP140 could influence risk through differing response to antigenic challenge as its coactivation may be important for establishment of latent viral infections and B-cell immortalization. 20 Genome-wide association studies have shown that the 128-to 130-Mb interval at 8q24.21 harbors multiple independent loci with different tumor specificities, even though it is bereft of genes. The colorectal-prostate cancer association affects TCF4 binding to an enhancer for MYC, providing a mechanistic basis for this 8q24.21 association.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is clear that many adenoviruses and herpesviruses encode regulatory proteins that localize to, and disrupt the functions of, PML nuclear bodies (reviewed by Everett & Chelbi-Alix, 2007). For example, to aid replication, the AdV E4orf3 protein reorganizes PML nuclear bodies into thread-like structures (Doucas et al, 1996;Stracker et al, 2005;Hoppe et al, 2006;Ullman et al, 2007); the ICP0 protein of HSV-1 has E3 ligase activity that induces the degradation of PML and SUMO-modified forms of Sp100 (reviewed by Hagglund & Roizman, 2004); EBV nuclear antigen 5 (EBNA5) interacts with Sp100A, but this may be to release PML-associated factors from PML nuclear bodies to aid viral gene expression (Ling et al, 2005); HCMV IE72 induces the loss of SUMO-modified forms of PML to disrupt PML nuclear bodies (Ahn & Hayward, 2000;Kang et al, 2006), and pp71 localizes to PML nuclear bodies to induce the degradation of hDaxx, which inhibits HCMV IE gene expression (Cantrell & Bresnahan, 2006;Preston & Nicholl, 2006;Saffert & Kalejta, 2006). Even certain RNA viruses that replicate in the cytoplasm may block PML function.…”
Section: General Considerations Of How Viruses Evade the Ifn Responsementioning
confidence: 99%